Nanomaterials as drug delivery agents for overcoming the blood-brain barrier: A comprehensive review - Mangesh Kulkarni; Krishi Patel; Ayush Patel; Swayamprakash Patel; Jagruti Desai; Mehul Patel; Umang Shah; Ashish Patel; Nilay Solanki (International Association of Physical Chemists (IAPC), 2023)
Background and Purpose: The blood-brain barrier (BBB), a critical interface of specialized endothelial cells, plays a pivotal role in regulating molecular and ion transport between the central nervous system (CNS) and systemic circulation. Experimental Approach: This review aims to delve into the intricate architecture and functions of the BBB while addressing challenges associated with delivering therapeutics to the brain. Historical milestones and contemporary insights underscore the BBB's significance in protecting the CNS. Key Results: Innovative approaches for enhanced drug transport include intranasal delivery exploiting olfactory and trigeminal pathways, as well as techniques like temporary BBB opening through chemicals, receptors, or focused ultrasound. These avenues hold the potential to reshape conventional drug delivery paradigms and address the limitations posed by the BBB's selectivity. Conclusion: This review underscores the vital role of the BBB in maintaining CNS health and emphasizes the importance of effective drug delivery through this barrier. Nanoparticles emerge as promising candidates to overcome BBB limitations and potentially revolutionize the treatment of CNS disorders. As research progresses, the application of nanomaterials shows immense potential for advancing neurological therapeutics, albeit with careful consideration of safety aspects.